QUALIDADE DE VIDA DAS FAMÍLIAS DE CRIANÇAS AUTISTAS - AYRES, Nicole Okushiro; GUIMARÃES, Leonardo Negrão; LOPES, Danilo; SAUER, Maria Inesila Montenegro; CERCHIARI, Ednéia Albino Nunes (ANAIS DO ENIC, 2018)
-